2020
DOI: 10.1186/s12951-020-00719-x
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the cellular response of silver nanoparticles as a potential combinatorial agent for cisplatin chemotherapy

Abstract: Background Combination chemotherapy uses drugs that target different cancer hallmarks, resulting in synergistic or additive toxicity. This strategy enhances therapeutic efficacy as well as minimizes drug resistance and side effects. In this study, we investigated whether silver nanoparticles act as a combinatorial partner to cisplatin. In so doing, we compared post-exposure biological endpoints, intracellular drug accumulation, and changes in the proteome profile of tumoral and normal cell line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…16 In the last years, the development of metallic nanoparticles has raised increased interest in the scientific community and AgNPs, specifically, have already shown cytotoxic potential in different tumor models. 25,[36][37][38] The increased glucose consumption in more advanced forms of PCa can be an opportunity to design AgNPs that specifically target cancer cells, through a glucose functionalization.…”
Section: Discussionmentioning
confidence: 99%
“…16 In the last years, the development of metallic nanoparticles has raised increased interest in the scientific community and AgNPs, specifically, have already shown cytotoxic potential in different tumor models. 25,[36][37][38] The increased glucose consumption in more advanced forms of PCa can be an opportunity to design AgNPs that specifically target cancer cells, through a glucose functionalization.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the inactivation of the drug resistance property in malignant cells may be generated by inactivating the efflux activity of multidrug resistance transporters in cancer cells. This is another proposed mechanism regarding the damage to cancer hallmarks that may be induced by AgNPs, particularly glucose metabolism and drug resistance (Rank et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Alkylation was performed using 300 mM iodoacetamide (IAA) for 30 min in the dark, following digestion with trypsin (1:100 w/w trypsin: protein) overnight, at room temperature. Finally, the peptides were acidified using 1% v/v formic acid to stop the trypsin digestion and lyophilized before desalting ( Rank Miranda et al, 2020 ). Samples were resuspended in 0.1% v/v trifluoroacetic acid (TFA) and desalted using ZipTipC18 Pipette Tip with C18 Resin (Sigma Aldrich, Brazil) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%